Addressing the Medical Mask Waste Crisis: Leveraging ThingLink and SSI-STEM to Foster Student Argumentation - Murni Ramli; Ani Satun Zahro; Alanindra Saputra (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
The surge in disposable medical mask waste during the post COVID-19 pandemic has created a significant environmental challenge, while the shift to distance learning has hindered the ability of teachers to effectively develop students' argumentation skills. This research aimed to: 1) evaluate the effect of a ThingLink-based Socio-Scientific Issues-Science Technology Engineering and Mathematics (SSI-STEM) approach on the argumentation skills of tenth-grade students; 2) profile students' argumentative abilities in solving environmental pollution problems; and 3) assess student responses to this integrated learning model. Utilizing a mixed-method triangulation design, the study involved 72 students divided into one control group (N=36) and experimental groups (N=36). The control group received standard SSI-STEM instruction, while the experimental group utilized the ThingLink-based SSI-STEM approach. Data were collected through pre- and post-tests and analyzed using paired-samples t-tests. Results indicated a significant improvement in argumentation skills (p < 0.05), with the experimental group achieving a higher average post-test score (76.3) compared to the control group (54.8). In particular, the percentage of students achieved the highest argumentation level (Level 6) increased to 39.4% in the experimental group, compared to only 7.2% in the control group. The students’ responses were highly positive, particularly regarding their interest in innovative solutions for medical mask waste. Ic can be concluded that the ThingLink-based SSI-STEM approach is an effective tool for improving 21st-century skills and environmental literacy in biology learning.